Accuracy of optical heart ratemeasurement and distancemeasurement of a fitness trackerand their consequential use insports - Budig, M.; Höltke, V.; Keiner, M. (German Journal of Exercise and Sport Research, 2019)
Background: The possibilities of continuously monitoring everyday training have become more varied and precise. Fitness trackers are common devices used for collecting training data. The aim of this study was to validate the optical heart rate (HR) and global positioning system (GPS) distance measurements under real conditions. Methods: In total, 30 moderate endurance-trained adults (15 males/15 females) completed a running test battery, 3 km of walking and running and 1.6 km of interval running, with optical HR measurement. The distance measurement test battery consisted of swimming for 500 and 1000 m, biking for 4.3 and for 36.7 km, stadium running for 3 km, walking and running for 1.6-km intervals, and off-road running for 3 and for 7.1 km. The criterion measurements consisted of HR measurement via chest strap and distance measurement via map in a 400-m stadium and 50-m pool. The differences between the measured HR/GPS distance data and the criterion measurement were calculated using several statistical methods. Results: The t-test analysis of HR measurements showed significant differences during the 1.6 km of interval running (p < 0.049) over seven phases and at resting HR (RestHR; p < 0.021). The false discovery rate (FDR) calculation showed similar results (p < 0.047; p < 0.026; effect sizes interval running d > 0.67; RestHR d > 1.12). The t-test analysis of distance showed significant differences in biking (p = 0.000) and running test results (p < 0.002). The effect sizes were d < -0.47 and d > 0.72, respectively. The median absolute percentage error (MAPE) was <2.75% for biking and running and <4.50% for swimming. Conclusion: This study showed significant inaccuracies in optical HR measurements during rapidly changing HRs in real field testing for the first time. The GPS measurements also showed significant differences, but MAPEs were negligible. Therefore, optical HR measurement should be used on a limited basis, while distance/speed control can be used without restrictions.